Hubungan Bimbingan Orang Tua Terhadap Kemampuan Membaca Anak Usia 5-6 Tahun - Azka Qisthiyah; Siti Azalea Malika; Zakia Maharani; Fidrayani Fidrayani (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2024)
This research analyzes the effect of parental guidance on the reading ability of children aged 5-6 years. Based on a systematic review of twelve articles, it was found that parents' active involvement in reading activities had a significant impact on children's reading abilities. Positive parenting patterns, such as democratic parenting, and the routine of reading together at home contribute greatly to the development of children's reading abilities. This research is a Systematic Review using the Preferred Reporting Items for Systematic Reviews and Meta-analyses method or commonly called PRISMA. The research sample consisted of twelve articles published in the 2019-2024 period. The results showed that children who received intensive guidance from parents showed significant improvements in reading ability compared to children who received minimal guidance. Parents' education and economic factors also influence the effectiveness of the guidance provided. This conclusion emphasizes the important role of parents in supporting early childhood reading development through positive and supportive interactions.